Pengaruh Corporate Social Responsibility terhadap pemberian keuntungan jangka panjang pemegang saham - Suhardjo, Iwan; Salmayani, Salmayani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Companies, as economic entities, regardless of the form of industry, aim to make optimal profits to increase the wealth of shareholders, but that alone is not enough. This study aims to find out what long-term benefits will exist for a company when it implements corporate social responsibility for its shareholders. This study uses a quantitative method, and data tests were conducted on 255 companies tested in 2017–2021. The data used has usually been distributed. The test results show that the obligation of CSR in a company has no significant positive effect on earnings persistence. This researcher proves that the fulfillment of CSR obligations in a company cannot guarantee the persistence of profits in that company. Furthermore, the authors claim that the obligation of CSR in a company has no significant positive effect on earnings persistence. This researcher proves that the fulfillment of CSR obligations in a company cannot guarantee the persistence of profits in that company.